Prebiotic synthesis from rice using Aspergillus oryzae with solid state fermentation - Sawangwan, Thornthan; Saman, Premsuda (Agriculture and Natural Resources, 2016)
Prebiotic synthesis from economical substrates (glutinous rice and rice bran) using Aspergillus oryzae TISTR 3102 and TISTR 3222 with solid state fermentation (SSF) was explored. The pH value, alphaglucosidase activity and total reducing sugar (TRS) concentration were monitored during incubation with different substrate ratios of 1:1 and 1:2 weight per weight (w/w). After 7 d incubation under SSF in glutinous rice and rice bran at 1:2 w/w, the highest alpha-glucosidase activity (4.49 Unit/mL) and TRS concentration (16.84 g/L) were detected. The product mixtures consisted of several reducing sugars as prebiotic compounds, especially panose and isomaltotriose. The prebiotic properties were investigated for their growth stimulation on two probiotic strains (Lactobacillus plantarum and Lactobacillus acidophilus) and the inhibition of two pathogens (Escherichia coli and Salmonella paratyphi). These product mixtures under solid state fermentation (SSF) using A. oryzae in variable rice ratios displayed high efficiency with regard to prebiotic properties and were deemed appropriate for prebiotic production.